Enterprise Resource Planning: Konsep, Pengembangan dan Implementasi - Yuniaristanto -; Erwin Zakiyah (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2006)
Enterprise uses ERP systems with considering four rationales namely technology, competitive, business process, and strategic. Evolution of ERP: 1960’s (Inventory Control), 1970’s (MRP-Material Requirement Planning), 1980’s (MRP II–Manufacturing Resources Planning), Mid 1990’s (ERP– Enterprise Resource Planning), 2000 onwards (ERP II–Collaborative Commerce). ERP systems is a software solution that addresses the enterprise needs. It takes the process view of an organization to meet the organizational goals and tightly integrates all functions in that organization. The frequently module in ERP used by companies is financial and accounting. ERP solutions could be developed by using internal resources, buy, and using external resources. Measurement of ERP project considers on intangible factors, hidden outcomes and the changing nature ofinformation technology.